Sucrose density gradient centrifugation separation of gold and silver nanoparticles synthesized using Magnolia kobus plant leaf extracts - Lee, So Hyun; Salunke, Bipinchandra K; Kim, Beom Soo (Biotechnology and bioprocess engineering, 2014)
The synthesis and post-synthesis separation of nanoparticles that are polydispersed in size and shape is important due to their variety of applications. In the present study, it is demonstrated that the Magnolia kobus plant extract produces a diverse mixture of extracellular gold and silver nanocrystals with a majority of polydispersed spheres; however, there are a significant number of homogeneously sized triangles, pentagons, and hexagons. The gold and silver nanoparticles synthesized using the M. kobus plant extract can be separated using density gradient centrifugation in the size range of 52 ∼ 117 nm and 38 ∼ 61 nm, respectively. The average particle sizes increase with increases in the sucrose concentration of each layer. Relatively larger but long, thin plates of gold nanoparticles appear in the higher density sediments, whereas a larger proportion of smaller spheres featured in the lower density gradients. Similarly, silver nanospheres of different sizes are separated at different density gradients with smaller proportions of plates.